Impact of glycoprotein IIb/IIIa inhibitors on the efficacy and safety of ticagrelor compared with clopidogrel in patients with acute coronary syndromes: analysis from the Platelet Inhibition and Patient Outcomes (PLATO) Trial - Shimada, Yuichi J.; Katus, Hugo (American heart journal, 2016)
Background: Ticagrelor reduced cardiovascular events compared with clopidogrel in PLATO without increasing overall major bleeding. We evaluated whether the use of glycoprotein IIb/IIIa inhibitor (GPI) impacts the relative efficacy and safety of ticagrelor compared with clopidogrel. Methods: PLATO randomized 18,624 subjects with acute coronary syndrome to ticagrelor versus clopidogrel. The primary efficacy end point was cardiovascular death/myocardial infarction/stroke, and the primary safety end point was major bleeding. The use of GPI was at the physician’s discretion and open-label. We evaluated outcomes at 30 days stratified by GPI use in the subgroup of 9,983 patients who underwent percutaneous coronary intervention (PCI) within 72 hours. Results: A total of 4,020 (40%) received a GPI. Those receiving a GPI were more likely to be younger, be male, and undergo multivessel PCI. There was no interaction between treatment and GPI use for the primary efficacy and safety end points. Patients treated without GPI had a lower rate of definite stent thrombosis and higher rate of minor/major bleeding with ticagrelor compared with clopidogrel (P < .05), whereas there was no such difference with GPI (P interaction < .05). Conclusions: In patients with acute coronary syndrome undergoing early PCI, the efficacy and safety of ticagrelor as compared with clopidogrel were not modified by GPI use according to the primary efficacy and safety end point of the trial, although there were indications of greater benefit on definite stent thrombosis and more major or minor bleeding with ticagrelor in patients without (vs with) GPI treatment.
Gesehen am 20.11.2018